Application of Vertical Electrical Sounding (VES) for Subsurface Profiling in Weh Island, Aceh Province - Marwan Marwan; Rifqan Rifqan; Idris Syafrizal; Yanis Muhammad (Graduate Program of Syiah Kuala University, 2019)
Groundwater availability is the main concern in a developing region such as Weh Island, Aceh. To locate groundwater resources, vertical electrical sounding (VES) was used to identify subsurface profiles. The study area is located on a volcanic island. The lithology consists of volcanic rocks as andesite lava and pyroclastic rocks as lapily-tuff until breccia. VES method was carried out in 4 measurement points using the Schlumberger array. The resistivity value used to identify subsurface lithology. The top layer of alluvium and weathered lava have resistivity ranges from 14.3 Ωm to 17.7 Ωm with thickness varies from 0 m – 17.4 m. It is followed by andesite resistivity ranges from 17.3 Ωm to 18.2 Ωm with averages thickness is 17.4 m – 35.2 m. Finally, the bottom layer is filled by breccia-tuff with resistivity value from 5.5 Ωm to 7.3 Ωm. The physical properties of some related rocks allow water accumulation to their bodies. The current polarization indicates water content in the pore space of breecia at the study area which polarization point is identified as the water table.